2013
DOI: 10.4038/cmj.v58i4.6304
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of renal histology in asymptomatic patients with probable chronic kidney disease of unknown aetiology in Sri Lanka

Abstract: The early disease among asymptomatic patients is characterized by interstitial fibrosis without significant interstitial inflammation and glomerular sclerosis with preserved glomerular function. Although the role of interstitial inflammation in the initiation of the disease is not clear, it appears to have a role in the progression of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 18 publications
1
44
0
5
Order By: Relevance
“…The earliest pathological manifestation was interstitial inflammation and interstitial fibrosis, whereas tubular atrophy and glomerulosclerosis were seen in later stages. 23 …”
Section: Methodsmentioning
confidence: 99%
“…The earliest pathological manifestation was interstitial inflammation and interstitial fibrosis, whereas tubular atrophy and glomerulosclerosis were seen in later stages. 23 …”
Section: Methodsmentioning
confidence: 99%
“…Tubulointerstitial disease is a prominent feature in subjects with suspected CKDu. 15,16,20,22,23 A recent study in asymptomatic CKDu patients with proteinuria showed that the majority of subjects had varying degrees of interstitial fibrosis, interstitial inflammation, glomerulosclerosis, and tubular atrophy. 18 In this study, interstitial fibrosis in more than 5% of cortical area was seen in 93% of study subjects.…”
Section: Histopathological Findings In Ckdumentioning
confidence: 99%
“…18 Nonetheless, it is postulated that interstitial inflammation may play a role in the progression of the disease. 20,23 Another study conducted between 2008 and 2009 demonstrated glomerular changes, included global sclerosis (37.1%), ischemic-type obsolescence, wrinkled and collapsed glomerular tufts (17.6%), and glomerular enlargement (36%). 18 Focal segmental glomerulosclerosis was uncommon (3.6%).…”
Section: Histopathological Findings In Ckdumentioning
confidence: 99%
“…Because the cause remains unknown, the disease is also called "CKD of unknown origin" (CKDu) [4][5][6]. In disease-affected that of CKDmfo [20][21][22][23]. CKDmfo is a tubular disease and thus, protein urea is a late manifestation.…”
Section: Introductionmentioning
confidence: 99%